Business Process Automation as an Innovative Strategy in Modernizing Corporate Business Administration - Prayitno, Arief (Journal of Management, 2023)
This study aims to analyze the role of business process automation as an innovative strategy in driving the modernization of business administration. Amid the rapid development of digital technology, organizations are required to enhance efficiency, accuracy, and speed in administrative management. Automation serves as a strategic solution to replace manual processes that tend to be slow and prone to errors. The research method used is a descriptive approach with qualitative analysis of the implementation of automation across various business sectors. Data were collected through interviews, literature studies, and observations of digital system-based administrative practices. The findings show that business process automation significantly contributes to the modernization of business administration by positively impacting operational efficiency, data accuracy, information-based decision-making, and customer service quality. Through the integration of Business Process Automation (BPA), companies are able to streamline various processes such as employee onboarding, purchase order management, contract management, marketing, and sales, thereby reducing reliance on manual processes that are susceptible to errors and delays. These findings reinforce that automation not only boosts productivity and reduces costs but also accelerates business responsiveness to market dynamics, enhances competitiveness, and strengthens the organizational foundation for long-term growth in a technology-driven business environment.